Oxidative stability of tocochromanols, carotenoids, and fatty acids in maize (Zea mays L.) porridges with varying phytate concentrations during cooking and in vitro digestion. (1st June 2022) - Lux, Peter E.; Fuchs, Larissa; Wiedmaier-Czerny, Nina; Frank, Jan
Highlights: Tocochromanols, carotenoids, and fatty acids in maize were decreased by cooking and digestion. Elevated concentrations of α-tocopherylquinone were found after in vitro digestion. Digestive stabilities of total tocochromanols and carotenoids were unaffected by phytate addition. Phytate significantly decreased micellarisation efficiencies of carotenoids in maize. Abstract: Phytic acid, the main storage form of phosphate in maize ( Zea mays L.) grains, is known as antinutrient due to its chelating properties but may also prevent oxidation. Thus, the impact of phytic acid on the degradation of tocochromanols, carotenoids, fatty acids, and oxidation products in maize during cooking and subsequent in vitro digestion was examined. Maize porridges from low phytic acid maize flour with or without admixed phytate, or from high phytic acid maize flour were prepared, and digestion experiments conducted. HPLC-(MS) or GC-MS analyses revealed a significant decrease in tocochromanols, carotenoids, and unsaturated fatty acids in the digesta compared to the maize porridges while α-tocopherylquinone and malondialdehyde concentrations increased. The addition of phytic acid did not affect the digestive stabilities of total tocochromanols and carotenoids, but increased micellarisation efficiencies of carotenoids. In conclusion, phytate did not exert antioxidant effects in maize porridge during cooking or simulated digestion.